2000
DOI: 10.1002/(sici)1098-2388(200001/02)18:1<52::aid-ssu8>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine treatment in prostate cancer

Abstract: Over its natural course, prostate cancer is a heterogeneous tumour with a generally slow but constant rate of growth. The androgen dependence of the prostate gland was demonstrated more than half a century ago by the landmark studies of Professor C. Huggins and colleagues. They established that androgens are implicated not only in growth regulation of the normal gland but also in the pathogenesis of prostate cancer, and that this malignant tissue retains some degree of androgen dependence. This concept was sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
117
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(119 citation statements)
references
References 105 publications
(99 reference statements)
1
117
0
1
Order By: Relevance
“…Both androgen and androgen receptor (AR) are recognized risk factors in the development of prostate cancer [17][18][19][20]. These observations are further corroborated by genetic evidence from transgenic mouse models, suggesting that increased AR signaling in the prostate is linked to an increase in precancerous lesions [21].…”
Section: Introductionmentioning
confidence: 54%
“…Both androgen and androgen receptor (AR) are recognized risk factors in the development of prostate cancer [17][18][19][20]. These observations are further corroborated by genetic evidence from transgenic mouse models, suggesting that increased AR signaling in the prostate is linked to an increase in precancerous lesions [21].…”
Section: Introductionmentioning
confidence: 54%
“…It has been shown that LH-releasing hormone (LHRH) agonists can transitionally stimulate serum testosterone release, and then reduce the level through blocking LH. 5 Treatment with the two antiandrogens here resulted in decreased expression of SV40 Tag via inhibition of AR function. The SV40 Tag acts as an oncoprotein through interaction with both retinoblastoma (Rb) 28 and p53 tumor-suppressor gene products.…”
Section: Resultsmentioning
confidence: 92%
“…4,5 Although androgen ablation at this hormone refractory stage is ineffective, androgen deprivation strategy as an early intervention may delay the promotion and/or progression of prostate cancer, resulting in reduced morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 80-90% of prostate cancers are dependent on androgens at initial diagnosis. Since the discovery by Huggins and Hodges (1941) that prostate cancer progression is influenced by androgen actions, androgen-deprivation therapy (ADT) to suppress androgens binding to androgen receptor (AR) remains the major treatment regimen for the disease (Denis and Griffiths, 2000). However, ADT ultimately fails, and prostate cancer progresses to a hormonerefractory (androgen-independent) state with advanced metastasis and high morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%